2023
DOI: 10.2147/prbm.s408276
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fitness Apps Usage Intensity on Exercise Adherence Among Chinese College Students: Testing a Moderated Mediation Model

Abstract: Purpose With the rapid development of media network technology, college students’ exercise is influenced by the use of fitness apps. How to improve the impact of fitness apps on college students’ exercise is a current research hotspot. The purpose of this study was to explore the influence mechanism of fitness apps usage intensity (FAUI) on college students’ exercise adherence. Methods A large sample of Chinese college students (N=1300) completed measures by using the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Some studies like that of Suh & Li [5] have found that fitness apps have beneficial effects to the user's health outcomes. The frequency of fitness apps utilization is positively associated with exercise adherence [6]. However, other studies like that of Milne-Ives et al [7] claim that there is no strong evidence supporting its effectiveness in physical activity improvements.…”
Section: Introductionmentioning
confidence: 98%
“…Some studies like that of Suh & Li [5] have found that fitness apps have beneficial effects to the user's health outcomes. The frequency of fitness apps utilization is positively associated with exercise adherence [6]. However, other studies like that of Milne-Ives et al [7] claim that there is no strong evidence supporting its effectiveness in physical activity improvements.…”
Section: Introductionmentioning
confidence: 98%
“…When individuals have positive experiences during exercise, such as feeling energized, accomplished and happy, they are more likely to continue exercising in the future, thus increasing their willingness to participate in sport [ 17 ]. Therefore, subjective exercise experience, as a self-evaluation of emotional feelings, has been suggested as a mediator between physical activity and exercise adherence [ 18 ]. Therefore, creating a positive and personalized exercise experience is an effective strategy to promote exercise adherence among college students.…”
Section: Introductionmentioning
confidence: 99%